Diameter-dependent electrochemical supercapacitive properties of anodized titanium oxide nanotubes. (15th July 2015) - Al-Osta, Ahmed; Jadhav, Vijaykumar V.; Saad, Nabil A.; Mane, Rajaram S.; Naushad, Mu.; Hui, K.N.; Han, Sung-Hwan
Graphical abstract: Abstract :   Electrochemical supercapacitors of titanium dioxide nanotubes (NTs) of various diameters were synthesized from ethylene glycol (EG), polyethylene glycol (PEG) and diethylene glycol (DEG) reagents using anodization process. NTs prepared from the EG were 100 (±20) nm whereas those obtained from PEG and DEG were 200 (±50) and 300 (±50) nm, respectively. Due to a diameter difference followed by charge transfer resistance, NTs obtained from EG, PEG and DEG demonstrated 14.39, 21.81, and 26.12 F g −1 specific capacitances, respectively.